Exclusive concurrent radiochemotherapy for advanced head and neck cancers with 'fractionated' 5-fluorouracil and cisplatin. Issue 2 (February 2017) - Peyraga, Guillaume; Linot, Benjamin; Yossi, Sena; Gustin, Pierre; Rousseau, Dominique; Septans, Anne-Lise; Breheret, Renaud; Laccourreye, Laurent; Rives, Pauline; Capitain, Olivier
Abstract : Concurrent radiochemotherapy (CRC) is a standard treatment in patients with inoperable locoregionally advanced ear–nose–throat (ENT) cancer. We report the safety and efficacy of CRC with daily fractionated 5-fluorouracil and cisplatin ('F' 5FU–CDDP) in a monocentric retrospective cohort. From January 2006 to August 2012, all patients with unresectable (or inoperable) nonmetastatic locoregionally advanced ENT cancer treated curatively by means of radiotherapy (normal fractionated 70 Gy to the macroscopic tumor and prophylactic 50 Gy) with three courses (week 1–week 4–week 7) of 'F' 5FU–CDDP regimen (800 mg/m 2 /day of 5-fluorouracil and 20 mg/m 2 /day of CDDP from day 1 to day 4) were included. Seventy patients underwent CRC (86% men, median age 58 years old, 100% squamous cell carcinoma, 97% stage III/IV). Fifty-six patients received the three complete courses of chemotherapy with cumulative doses of CDDP of 217 mg/m 2 /patient (dose intensity ratio of 90.5%). After a median follow-up period of 30.7 months, median overall and disease-free survivals were 34.1 [95% confidence interval (CI) (21.6–56.8)] and 50.2 months [95% CI (17.4–NA)] with 71% [95% CI (57.5–81)] and 67% [95% CI (51.8–78.5)] for locoregional control at 2 and 5 years, respectively. In all, 58.5% of grade 3 or higher mucositis and 24% of radioepithelitis were observed, but only 11.5, 3, and 1.5% of grade 3 or higher neutropenia, nephrotoxicity, and neurotoxicity were observed, respectively. No deaths from toxicity occurred. CRC with three courses of 'F' 5FU–CDDP appears effective and could be an alternative to standard CRC treatment. Randomized studies are required to be able to use this treatment regimen routinely.